Strengthening Student Organization Governance Through PPEPP Cycle-Based Micro-Leading Mentoring in an International Islamic Boarding School - Hasan Argadinata; Mustiningsih Mustiningsih; Rochmawati Rochmawati; Indra Lesmana; Bayu Bahari; Elyya Putri Fia Nurmaya; Anggit Rija Nurhidayat; Intan Kurniawati (Universitas Negeri Malang, 2026)
Student organizations in International Islamic Boarding Schools play a strategic role in fostering leadership, responsibility, discipline, and organizational culture among students. However, student organization administrators still require strengthening in aspects such as program planning, task distribution, documentation, evaluation, and follow-up of activities. This community service program aimed to strengthen student organization governance through PPEPP cycle-based micro-leading mentoring at International Islamic Boarding School Baitul Manshurin Malang. The target participants included student council members, student representative council members, extracurricular organization leaders, and student activity units. The program employed a Participatory Action Mentoring approach based on the PPEPP cycle, consisting of determination, implementation, evaluation, control, and improvement stages. Data were collected through pre-tests, post-tests, observations of leadership practices, governance product rubrics, participant reflections, and activity documentation. The results demonstrated an increase in the average participant score from 56.93 in the pre-test to 82.12 in the post-test, representing an improvement of 44.23% with an N-Gain score of 0.58, categorized as moderate. Improvements were also observed in documented work programs, meeting minutes, task allocation, activity evaluation, follow-up actions, and the archiving of activity evidence. The mentoring program produced PPEPP-based work program templates, evaluation forms, meeting minute formats, reporting templates, and periodic monitoring plans. These findings indicate that PPEPP cycle-based micro-leading mentoring is effective in strengthening student organization governance in a systematic, accountable, reflective, and sustainable manner.